Breaking Barriers: The Role of Women in Leadership within African Apostolic Indigenous Churches in Enhancing Gender Equality in Southern Africa - Tsara, Lindah (Journal of Ecohumanism, 2026)
This study examines the gendered leadership dynamics of women in African Apostolic Indigenous Churches (AAICs) in Southern Africa, with a specific focus on the Tangwena region. While AAICs assert their empowerment of women through inclusive participation in church activities such as preaching and prophesying, this research critically investigates the paradox of empowerment versus liberation within these organizations. The study addresses three key questions: the discrepancy between the empowerment claimed by AAICs and the lack of female representation in prestigious leadership roles; the lessons that can be derived from these churches regarding gender equity; and the importance of integrating women into leadership positions both within the church and the broader society. Employing qualitative research methods, including interviews and a literature review, this study reveals that, despite their active roles, women in AAICs face significant structural and cultural barriers that hinder their advancement to higher leadership positions. The findings suggest that while women are empowered in certain facets, they remain institutionalized within traditional gender norms, limiting their full liberation. The study advocates for a comprehensive acknowledgment of women’s status in AAICs. It urges transformative practices that facilitate their leadership potential, vital for achieving gender equity within the church and the community.